Complex Patterns of GABAergic Neuronal Deficiency and Type 2 Potassium-Chloride Cotransporter Immaturity in Human Focal Cortical Dysplasia. Issue 4 (11th March 2019) - Han, Pengcheng; Welsh, Cynthia T; Smith, Michael T; Schmidt, Robert E; Carroll, Steven L
Abstract: Focal cortical dysplasia (FCD) is a common histopathologic finding in cortical specimens resected for refractory epilepsy. GABAergic neuronal abnormalities and K-Cl cotransporter type 2 (KCC2) immaturity may be contributing factors for FCD-related epilepsy. We examined surgical specimens from 12 cases diagnosed with FCD, and brain tissues without developmental abnormality obtained from 6 autopsy cases. We found that GABAergic neuronal density was abnormal in FCD with 2 distinct patterns. In 7 of 12 (58%) FCD subjects, the GABAergic neuron density in dysplastic regions and in neighboring nondysplastic regions was equally reduced, hence we call this a "broad pattern." In the remaining cases, GABAergic neuron density was decreased in dysplastic regions but not in the neighboring nondysplastic regions; we designate this "restricted pattern." The different patterns are not associated with pathologic subtypes of FCD. Intracytoplasmic retention of KCC2 is evident in dysmorphic neurons in the majority of FCD type II subjects (5/7) but not in FCD type I. Our study suggests that (1 ) "broad" GABAergic deficiency may reflect epileptic vulnerability outside the dysplastic area; and (2 ) abnormal distribution of KCC2 may contribute to seizure generation in patients with FCD type II but not in type I.